2023
DOI: 10.1039/d3dt01651j
|View full text |Cite
|
Sign up to set email alerts
|

Tetracopper(i) thiolate- and amido-(SNS) complexes and copper-catalyzed azide–alkyne cycloaddition in water

Atousa Khanzadeh,
Saeed Ataie,
R. Tom Baker

Abstract: Two tetranuclear Cu(I) complexes bearing thiolate- and amido-SNS ligands were characterized by X-ray diffraction and mass spectrometry. Although the amido ligand undergoes irreversible N-protonation by the copper-bound alkyne, the thiolate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Using weaker acids such as H 2 O, tert -butanol and methanol resulted in a similar brown-yellow solution that gradually turned brown-black with some precipitate formed. In a recent study we observed that treatment of [CuL 1 ] 4 with H 2 O liberated L 1 H . The paramagnetic 1 H NMR spectrum of Co-2 showed two singlets at δ 0.74 and 0.95, each due to two SMe groups (Figure S1).…”
Section: Resultssupporting
confidence: 81%
“…Using weaker acids such as H 2 O, tert -butanol and methanol resulted in a similar brown-yellow solution that gradually turned brown-black with some precipitate formed. In a recent study we observed that treatment of [CuL 1 ] 4 with H 2 O liberated L 1 H . The paramagnetic 1 H NMR spectrum of Co-2 showed two singlets at δ 0.74 and 0.95, each due to two SMe groups (Figure S1).…”
Section: Resultssupporting
confidence: 81%